“Killing an arab” by The Cure: is this a racism? - Rizqi Husaini; Rida Fahas (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
This study aims to find out about everything that is in the song "Killing an Arab" which was popularized by The Cure. The research uses a qualitative approach that focuses on analyzing the content of the song. The data was obtained from documentation and observations of several articles both related to the song and articles about the phenomenon of racism. The result of the research is this song has a meaning that is difficult to interpret. Whether or not this song is racist depends on the perspective of each listener in interpreting this lag. The Cure's objection that this song does not contain racism clearly refutes everything that develops in society. But still for the racism in this song will never go away. Because everyone's perspective is different in interpreting this song.